Global Mindset and International Business Driving Process Outsourcing Organizations - Kossowska, Magdalena (Routledge Studies in International Business and the World Economy, 2024)
Global mindset is an emerging concept, influenced by globalization, that can support companies' growth in international settings and help develop a more effective, skilled workforce that can be open and adaptable. This book presents an analysis of current global mindset knowledge and explores how national culture and international business behaviors affect global mindset development in business process outsourcing organizations in both managerial and non-managerial groups. The authors outline how processes of skill development and their final impact differ within multinational enterprises among managers and non-managers and present the implications on how to apply it in various seniority, talent groups. The theoretical and practical research discusses and emphasizes the need to involve employees in international relationship building, developing international know-how, and focusing on the methods of communication and management in business, because they stimulate the development of global mindset among managers and non-managers contributing to further business success. This book will find an audience with researchers and astute students within international business, cross-cultural management, and business process outsourcing in particular. It will also be a valuable resource for those researching and operating in global teams.